A narrative review of proteinuria and albuminuria as clinical biomarkers in children. (9th November 2018) - Larkins, Nicholas G; Teixeira‐Pinto, Armando; Craig, Jonathan C
Abstract: Proteinuria is an important biomarker commonly used to detect and manage kidney disease in children. There are now a variety of methods available to measure urinary protein loss, and physicians are faced with several contrasting strategies: 24‐h or timed collection versus spot samples (first‐morning or random), measurement of total urinary protein versus selective measurement of urinary albumin, unadjusted urine protein concentration versus protein‐to‐creatinine ratio and the use of dipstick versus laboratory‐based methods. In this review, we will discuss the advantages and disadvantages of these different approaches. We will then summarise the evidence base for proteinuria as a clinical biomarker in different settings, including discussion of the current and potential role of measuring low‐level albuminuria. Finally, we will highlight gaps in the literature and opportunities for further research into proteinuria among children.